The Relationship Between Perceived Emotional Intelligence and Late Adolescent Autonomy - Permatasari, Nirwana; Anwar, Shafira Rezky; Rustham, A. Tenri Pada (Golden Ratio of Social Science and Education, 2021)
This study aims to determine the relationship between perceived emotional intelligence and late adolescent autonomy in Makassar City. This study uses quantitative methods with a correlational research design. The Trait Meta-Mood Scale-30 (TMMS-30) and adolescent autonomy scale were given to the research sample selected by purposive sampling method, totaling 453 respondents of adolescent aged 18-21 years; data college use online survey. The object of study is located in Makassar City and identifying themselves Bugis ethnicity. The demonstration and data analysis results using the Bivariate Pearson correlation test showed a positive (unidirectional) relationship between perceived emotional intelligence and late adolescent autonomy. However, the relationship between these variables was moderate (R-calculated = 0.417; with Sig. level < 0.01). The demonstration of the correlation of these variables means that the higher the level of perceived emotional intelligence possessed by adolescents is in line with the level of autonomy of adolescents. However, our study also underlines that the ability of perceived emotional intelligence in predicting the autonomy factor of adolescents is in the moderate category. It is assumed that the control of the perceived emotional intelligence variable is not strong enough to justify its role in the autonomy of late adolescents in this study.